Inaugural Lecture: Surviving childhood trauma :a story between you and me - Siti Raudzah, Ghazali (Universiti Malaysia Sarawak (UNIMAS), 2015)
Surviving Childhood Trauma: a story between you and me reflects my many years of clinical experience in this field. Although I have been preoccupied, often overwhelmed, by the many things that I have to accomplish as an academician, as the years passed, I find myself enriched by these experiences. This book is a summary of many cases that have been related by my patients, students, research participants, and clients about their childhood trauma. Serving them in a professional capacity as a clinical psychologist, a lecturer, and a researcher has indeed been a privilege and comfort to my soul. The target audience of this book is the general public, who may not be familiar with the psychological health sciences. Specialist terminology and technical vocabulary has been purposely abandoned where possible in an effort to make this book as easy to read and as accessible to a generalist audience as possible. The background and personally identifying information of the individuals featured in these stories has been withheld or changed as appropriate to uphold confidentiality.